McCune-Albright syndrome: report of a male patient - Bilginturan, Nihat (The Turkish Journal of Pediatrics, 1965)
Our patient showed bone lesion of the skull and high 17-ketosteroid value. On the other hand he showed FSH level 6.6 mouse units which is within normal limits for adolescent males. On the basis of a normal FSH level and high 17-ketosteroid value we consider it as precocious puberty rather than sexual precocity. In that respect our patient appears unique in that, to our knowledge, this is the first reported case of McCune-Albright Syndrome in which sexual precocity is associated with mature gonadal functions.